Personnel Policy from the 25 Year Perspective in Municipal Offices - Kozłowski , Andrzej J. (Studia Oeconomica Posnaniensia, 2016)
Efficient management in the public sector aims primarily at the rational use of resources in this sector. This is possible only in the case of delegating the implementation of the tasks of skilled staff of officials, the modern managers of the public sector. The modern state of personnel in the public administration of Poland has developed in the process of change in the political, social, and economic systems. The general question that was researched on the state of personnel in public administration is whether in the past 25 years in Poland changes have occurred, what changes have happened, whether these changes are in accordance with the expectations of civil society, and finally, whether one can talk about cultivating a new management in the public sector in western European civilization. The problem discussed in the article is the state of the personnel officials in Poland, particularly personnel at the lowest level in the structure of state management, and particularly featured officials that are important in proper management. The test results have been carried out by the author since 1984 among administrative staff, and also among the members of the forming bodies and residents relating to the assessment of the qualification of officials and their impact in solving the issues of fundamental importance for citizens. The article relies primarily on the test results presented in the published monographs in subsequent decades of that period, and on the latest tests from 2014. In the article, alongside the proposals presented will be recommendations indicating the need for change in the system of HR policy in public administration.